Vision beyond visual perception - Toyota, Junichi, 1973-; Richards, Ian, 1958-; Kovačević, Borko; Shchepetunina, Marina (Cambridge Scholars Publishing, 2017)
"Vision is crucial for the survival of all animals. However, as this book shows, its importance does not simply lie in visual perception, but is, rather, deeply rooted in human physiology, psychology and culture. For instance, conceptual metaphors often involve vision, such as "Seeing is Touching" and "Eyes are Limbs", among others. However, this Anglo-centric linguistic view belies the fact that vision is not a universally-preferred source for metaphor, and less studied languages spoken in the four corners of the world can present cases that are unfamiliar to those who are only acquainted with Indo-European languages and cultures. In fact, other types of perception such as hearing are often preferred as a source of comprehension in a number of languages. This volume studies various issues concerning vision both synchronically and diachronically. Its discussion involves specialists from different disciplines, ranging from cognitive science to literary scholarship. It also covers a wide range of geographical regions, such as Africa and Asia. As such, this volume will serve to shed light on the integration of disciplines concerning vision."--Back cover